2016
DOI: 10.1515/abcsb-2016-0008
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear DNA Content and Ploidy Level of Apple Cultivars Including Polish ones in Relation to Some Morphological Traits

Abstract: Apple species and cultivars differ in nuclear (2C) DNA content and ploidy level. The majority of these genotypes are diploids, but there are some triploids and a few tetraploids. Nuclear DNA content is a specific feature and its flow cytometric evaluation can be helpful in differentiating taxa. For many apple genotypes -including all the Polish ones, these characteristics are not known. 2C DNA was evaluated in relation to leaf, flower, fruit, pollen grain and stomata sizes as well as to the flowering time for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Some studies reported spontaneous chromosome doubling as a side effect of in vitro multiplication (Barow and Jovtchev 2007;Chen et al 2009;Meyer et al 2009). Podwyszyńska et al (2016) examined the ploidy of 70 apple genotypes and found that polyploids had larger vegetative (stomata, leaves) and reproductive (flowers) characters, and fruits, suggesting that there is practical value to inducing polyploids in vitro. The polyploidization of apple in vitro has been achieved with colchicine and oryzalin (Bartish et al 1999;Ou et al 2008), but given the toxicity associated with the former (Spiller 2014), several polyploidization agents were compared by Podwyszyńska et al (2017), namely colchicine, trifluralin, oryzalin or amiprophos methyl (APM).…”
Section: Induction Of Polyploidization In Vitromentioning
confidence: 99%
“…Some studies reported spontaneous chromosome doubling as a side effect of in vitro multiplication (Barow and Jovtchev 2007;Chen et al 2009;Meyer et al 2009). Podwyszyńska et al (2016) examined the ploidy of 70 apple genotypes and found that polyploids had larger vegetative (stomata, leaves) and reproductive (flowers) characters, and fruits, suggesting that there is practical value to inducing polyploids in vitro. The polyploidization of apple in vitro has been achieved with colchicine and oryzalin (Bartish et al 1999;Ou et al 2008), but given the toxicity associated with the former (Spiller 2014), several polyploidization agents were compared by Podwyszyńska et al (2017), namely colchicine, trifluralin, oryzalin or amiprophos methyl (APM).…”
Section: Induction Of Polyploidization In Vitromentioning
confidence: 99%
“…are explained in detail by Greilhuber et al (2005). Furthermore, analytical tools such as flow cytometry are a reliable and convenient method to estimate genome size of plant communities such as ornamental plants (Abedi et al, 2015), medicinal plants (Javadian et al, 2017;Mahdavi and Karimzadeh, 2010;Majdi et al, 2010;Sadat Noori et al, 2017;Tarkesh Esfahani et al, 2016;Tavan et al, 2015) and fruit trees such as peach (Baird et al, 1994), olive (Brito et al, 2008;Loureiro et al, 2007b), coconut (Freitas et al, 2015), and Malus species (Hofer and Meister, 2010;Korban et al, 2009;Podwyszy nska et al, 2016). Unlike other fruit trees and plant species, there has been no study on the genome size of different walnut genotypes and cultivars, only flow cytometry is used to determine the ploidy level of walnut samples in in vitro conditions with the aim of identifying haploid plants (Sadat Hosseini Grouh et al, 2011).…”
mentioning
confidence: 99%
“…For genotypes within a species and genus, the higher ploidy level is generally associated with increased sizes of stomata and leaves as, e.g., in tea (Wachira, 1994), banana and plantain (Vandenhout et al, 1995) or mulberry (Laltanmawii, Roychowdhuri, 2010). Although, in Prunus rootstocks, comparison of averages for ploidy levels showed a certain tendency to increase the stomata and leaf size along with an increase in the ploidy level; however, the correlations between these traits were not so evident within the genus Prunus (plum and cherry rootstocks) as compared to the high positive correlation between nuclear DNA amount and stomatal length found for the cultivars of the species Malus × domestica (Tatum et al, 2005;Korban et al, 2009;Podwyszyńska et al, 2016). This probably results from the fact that the genus Prunus includes many various species and hybrids, for which phenotypic and genetic variability is much higher compared to variability of the cultivars within one species such, e.g., Malus × domectica.…”
Section: Discussionmentioning
confidence: 87%
“…And this species was reported to have larger genome compared to other diploid species (Arumuganathan, Earle, 1991;Dickson et al, 1992). Such differences in nuclear DNA contents between cultivars or species possessing the same chromosome number and belonging to the same genus are widely known in other genera, e.g., Lilium (Van Tuyl, Boon, 1997), Malus (Korban et al, 2009;Podwyszyńska et al, 2016); Tulipa (Zonneveld, 2009) and Narcissus (Zonneveld, 2010). The nuclear 2C DNA content is therefore considered as one of the taxa descriptors.…”
Section: Discussionmentioning
confidence: 93%